2015
DOI: 10.1163/22134808-00002495
|View full text |Cite
|
Sign up to set email alerts
|

The Moving History of Vestibular Stimulation as a Therapeutic Intervention

Abstract: Although the discovery and understanding of the function of the vestibular system date back only to the 19th century, strategies that involve vestibular stimulation were used long before to calm, soothe and even cure people. While such stimulation was classically achieved with various motion devices, like Cox's chair or Hallaran's swing, the development of caloric and galvanic vestibular stimulation has opened up new possibilities in the 20th century. With the increasing knowledge and recognition of vestibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 144 publications
(95 reference statements)
0
22
0
Order By: Relevance
“…The vestibular system plays the primary role in children's development. Its proper functioning is manifested in the ability to perform simple and complex motor activities, dealing with the activities of daily living (such as dressing, tying shoes, reading, writing, drawing) [15,16,17]. The aspect of equilibrium is an intrinsic part of every activity undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…The vestibular system plays the primary role in children's development. Its proper functioning is manifested in the ability to perform simple and complex motor activities, dealing with the activities of daily living (such as dressing, tying shoes, reading, writing, drawing) [15,16,17]. The aspect of equilibrium is an intrinsic part of every activity undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular stimulation has been used as a soothing and calming intervention during the treatment of various psychiatric and neurological diseases (Grabherr et al, 2015). Several studies, investigating the relationship between vestibular stimulation and sleep, have suggested that motion can be used to alter and possibly promote sleep.…”
Section: Introductionmentioning
confidence: 99%
“…CVS has been used diagnostically for decades, and there have been a number of small studies using CVS in a therapeutic context (e.g., Kolev, 1990;Rode et al, 2002;McGeoch et al, 2008McGeoch et al, , 2009Grabherr et al, 2015), but diagnostic-style CVS devices, which use water or air to flood the ear canal, are not amenable to home use. Current GVS devices are also not easily adapted for home use because of the need to clean the skin carefully, FIGURE 7 | Neurological disease represented as weak or broken network connections.…”
Section: Vestibular Neuromodulation Therapymentioning
confidence: 99%